1994
DOI: 10.1016/0370-2693(94)90655-6
|View full text |Cite
|
Sign up to set email alerts
|

String propagation in gravitational wave backgrounds

Abstract: The Conformal Field Theory of the current algebra of the centrally extended 2-d Euclidean group is analyzed. Its representations can be written in terms of four free fields (without background charge) with signature (−+++). We construct all irreducible representations of the current algebra with unitary base out of the free fields and their orbifolds. This is used to investigate the spectrum and scattering of strings moving in the background of a gravitational wave. We find that all the dynamics happens in the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
253
1

Year Published

1995
1995
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 106 publications
(267 citation statements)
references
References 29 publications
(27 reference statements)
13
253
1
Order By: Relevance
“…This is a manifestation of the underlying Scherk-Schwarz mechanism responsible for the spontaneous breaking of the N = 4 supersymmetry. The same conclusion can be reached by analysing the behaviour of the (T -and U-dependent) mass of the two gravitinos (see [2] and [21]). For λ = 0 ground states, there are two inequivalent limits in the (T, U) moduli where the masses of both gravitinos either vanish or become infinite.…”
Section: Decompactification Limits and Restoration Of N = 4 Supersymmsupporting
confidence: 59%
See 4 more Smart Citations
“…This is a manifestation of the underlying Scherk-Schwarz mechanism responsible for the spontaneous breaking of the N = 4 supersymmetry. The same conclusion can be reached by analysing the behaviour of the (T -and U-dependent) mass of the two gravitinos (see [2] and [21]). For λ = 0 ground states, there are two inequivalent limits in the (T, U) moduli where the masses of both gravitinos either vanish or become infinite.…”
Section: Decompactification Limits and Restoration Of N = 4 Supersymmsupporting
confidence: 59%
“…In Ref. [2] it was shown that there are perturbative heterotic ground states where supersymmetry is spontaneously broken from N = 2 down to N = 1, which possess a chiral four-dimensional spectrum. This opens more possibilities in string model-building, and obviously a more careful investigation is required when N > 1 is spontaneously broken to chiral N = 1 models.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations